American Theatre. - Gordon, John C. (photographer):::Creator::::::::::::
American theatre, renamed Beatty's American Theatre in 1921 by owner James Beatty. Photograph shows theatre audience waiting in line outside of theatre. This theatre was originally designed in a Spanish Gothic hybrid style in a collaboration of local architects Binder & Curtis with San Francisco architects Charles Peter Weeks & William Day. The Theatre was constructed in 1904.